Odpowiedzi

Najlepsza Odpowiedź!
2010-02-27T21:17:17+01:00
X:(-1 3/4)=1 1/3
zamieniam na ułamki bez części jednostkowych:
x : (-7/4) = 4/3 /* 4/7
-x = 16/24 /*(-1)
x = -16/24
skracamu ułamek:
x = -2/3



7 1/6-x=9 1/2
zamieniam na ułamki bez części jednostkowych:
43/6-x = 19/2
sprowadzam uł. do wspólnego mianownika (do 6)
43/6-x = 57/6 /-43/6
-x = 14/6 /*(-1)
x = - 14/6
x = - 2 i 1/3
2010-02-27T21:17:21+01:00
A.
x:(-1i3/4)=1 1/3

x:(-7/4)=4/3 /*(-4/7)
x=-16/21

B.
(7 i 1/6)-x=(9 i 1/2) /+x
(7 i 1/6)=(9 i 3/6)+x /-(9 i 3/6)
(7 i 1/6)-(9 i 3/6)=x
-2 i 2/6=x
x=-2 i 1/3
  • Użytkownik Zadane
2010-02-27T21:18:24+01:00
X:(-7/4)=4/3
x=(4/3)*(-7/4)
x=-7/3

7 1/6-x=9 1/2
43/6-x=19/2
43/6=19/2+x
x=(43/6)-(19/2)
x=(43/6)-(57/6)
x=-14/6=-2 1/3